Audiological findings in aphasic patients after stroke - Onoue,Solange Satie (2014)
Objective To outline the audiological findings of aphasic patients after cerebrovascular accidents.Methods This is a cross-sectional study performed between March 2011 and August 2012 in the Speech, Language, and Hearing Pathology Department of theUniversidade Federal de São Paulo. A total of 43 aphasic subjects (27 men) were referred for audiological evaluation after stroke, with mean age of 54.48 years. Basic audiological evaluation tests were performed, including pure tone audiometry, speech audiometry (speech recognition threshold and word recognition score), immittance measures (tympanometry and contralateral acoustic reflex), and transient otoacoustic emissions.Results Sensorineural hearing loss was prevalent (78.6%). Speech recognition threshold and word recognition score were not obtained in some patients because they were unable to perform the task. Hearing loss was a common finding in this population.Conclusion Comprehension and/or oral emission disruptions in aphasic patients after stroke compromised conventional speech audiometry, resulting in the need for changes in the evaluation procedures for these patients.